Musical Sound Processing - Kasri, Nurulwizana (Universiti Sains Malaysia, 2006)
Digital signal processors are used in a large variety of today’s domestic and industrial applications. This research emphasizes on the principle and techniques on audio processing field. This research focus on the basic issues involved in the design and implementation of digital audio effects with digital signal processor. The scope of this project was carried out into 3 main parts. Part one involves creating the basic sound effects which is echo, reverberation and flanging. It created using MATLAB and SIMULINK. Part two was studying the architecture of TMS320C6416 DSP Processor and the last part was implementation using TMS320C6416 DSP Processor Board. As results these three sound effects can be heard and comparison between echo and reverberation can be performed. Usually these three basic effects manipulated by sound engineer to add special audio effects in music audio and other applications. The Echo effect is very simple and is not suggested to be used in place Reverb effect such as hall, stage and other place especially enclosed buildings. Usually these places have to be designed such that the reverberation time is adequate for the type of sound that will be produced. These sound effects can improve the quality of performance in audio and movie applications.